Information system for monitoring of urban air pollution by heavy metals - Zhanar Oralbekova; Zarına Khassenova; Bakhyt Mynbayeva; Makpal Zhartybayeva; Kazizat Iskakov (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The authors of the article formulated the information monitoring system of Almaty city (The Republic of Kazakhstan). One of the urgent problems of the modern world is the ecological safety of the urban environment. The well-known unfavorable natural and anthropogenic factors of the Almaty city include the following: geographical and climatic features of the area, the lack of technologies for monitoring atmospheric air and traffic jams. All of the above factors increase the emissions of pollutants into the atmosphere, in particular, toxic heavy metals. A promising direction for solving this problem is the development of real-time monitoring using a mathematical model of data assimilation and the creation of software that allows you to assess the state of the system in real time. In this regard, this article describes the developed information system for the algorithm of data assimilation that optimizes the process of monitoring atmospheric air pollution with heavy metals.